Nikto ne zabyt . Nikto ne zabyt . Nobody is Forgotten . Никто не забыт - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The program shows the listing of the soldiers World War I, who had been are considered missing in action, and whose remains have been found by search brigades. Contributors: Kolin, Oleg (Anchor) Передача показывает список солдат Второй Мировой войны, которые до сих пор числились пропавшими без вести, и останки которых были недавно найдены поисковыми отрядами. Создатели: Колин, Олег (Ведущий/Ведущая)